2003
DOI: 10.1016/s0195-668x(03)00207-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of treatment strategies and survival in acute myocardial infarction: a population-based study in the Florence district, Italy Results of the acute myocardial infarction Florence registry (AMI-Florence),,

Abstract: In this unselected series of patients, primary PCI, routinely performed in high volume centres, achieved good results in terms of survival even outside the setting of a randomised clinical trial. However, the relatively high number of untreated subjects and the tendency to select less severe cases of AMI for reperfusion treatment confirm the need for an accurate reassessment of behavioural patterns in selecting patients for revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 23 publications
10
48
0
Order By: Relevance
“…[41] Clearly, all phases of intervention need to be considered to address the problem of AMI mortality: notwithstanding improvements in AMI treatment and serious efforts at primary prevention, AMI continues to cause millions of deaths worldwide. [3,42,43] In our study, as in other countries, men had higher AMI mortality rates then women, a pattern similar to that of Despite declining mortality rates, absolute numbers of AMI deaths continue to rise because of population aging, one of the most signifi cant demographic and social consequences of declining fertility and increased life expectancy. [12,22] We found that AMI mortality rates increased with age, independent of sex, which may be explained in part by its association with atherosclerosis and numerous age-related risk factors.…”
Section: Discussionsupporting
confidence: 84%
“…[41] Clearly, all phases of intervention need to be considered to address the problem of AMI mortality: notwithstanding improvements in AMI treatment and serious efforts at primary prevention, AMI continues to cause millions of deaths worldwide. [3,42,43] In our study, as in other countries, men had higher AMI mortality rates then women, a pattern similar to that of Despite declining mortality rates, absolute numbers of AMI deaths continue to rise because of population aging, one of the most signifi cant demographic and social consequences of declining fertility and increased life expectancy. [12,22] We found that AMI mortality rates increased with age, independent of sex, which may be explained in part by its association with atherosclerosis and numerous age-related risk factors.…”
Section: Discussionsupporting
confidence: 84%
“…Before admission, all patients had undergone primary PCI, which is the only reperfusion strategy for STEMI at Azienda OspedalieroUniversitaria Careggi, with no age restriction. [8][9][10] Inclusion criteria for direct primary PCI were: chest pain ≥30 min with ST-segment elevation on ECG ≥0.1 mV in ≥2 con-…”
Section: Methodsmentioning
confidence: 99%
“…Regarding cardiac emergencies, Careggi hospital is also the referring center for four community hospitals (the furthest being 50 km away from Careggi), located in the so-called area Vasta. In our hospital, in Florence, the reperfusion strategy of STEMI patients is represented by primary PCI [16][17][18]. STEMI patients are first evaluated by the Medical Emergency System staff in the pre-hospital setting and then directly admitted to the catheterization laboratory or transferred to it after a rapid stabilization in the first aid.…”
Section: Study Populationmentioning
confidence: 99%